The Use of Joox Application to Improve Students’ Listening Skill at the Eleventh Grade of SMK La-Tahzan Munjul Pandeglang in Academic Year 2022/2023 - Deliyanti, Dian; Riandi, Riandi; Novari, Ari Fajria (Universitas Mathla'ul Anwar Banten, 2023)
This research aimed to examine the use of Joox application as a media in teaching listening skill at the eleventh grade of SMK La-Tahzan Munjul in academic year 2022/2023. This research used quantitative approach with quasi experimental method. Achievement test is used in collecting the data, included pre-test and pot-test. Joox application is used as a teaching learning media. The population of this research is the eleventh grade of SMK La-Tahzan Munjul Pandeglang in academic year 2022/2023. The sample of this research is class XI Software Engineering and XI Computer and Network Technique, each class consists of 26 students. The researcher conducted the data by giving the test to both classes. The form of the test is multiple choice and error recognition with 25 total numbers of question given. The result of the research showed any improvement in learning outcomes through the use of Joox application as a media in English subject. It can be seen from the result of T-test by obtaining an average result 37.8 for pre-test and 77.4 for post-test in experimental class, by comparing T-count with T-table, because T-table is bigger than T-count or 1,706 > -26,955, then H0 is rejected and Ha is accepted. As a result, there is a significant improvement of using Joox Application on the students’ listening skill at the eleventh grade of SMK La-Tahzan Munjul Pandeglang in academic year 2021/2022.